Dimorphic Response of Neurons to Estrogen - Ziebart, Benjamin (My University, 2014)
A large part of the damage done to the brain during a stroke is due to the toxicity of glutamate. Glutamate is a neurotransmitter used to signal between cortical neurons which can be fatal to neurons in large surges. 17 beta-estradiol (E2) levels in the brain have previously been shown to provide neuroprotection against glutamate toxicity in healthy female neurons but not male neurons. The purpose of this study was to determine what role the cAMP response element binding (CREB) protein played in sexually dimorphic neuroprotection caused by E2.
Color poster with text, charts, images, and graphs.
Keywords: Neuroprotection--Sex difference; 17 beta-estradiol (E2); cAMP response element binding (CREB) protein; Stroke; Glutamate; Posters